4-[(1-Benzyl-1H-1,2,3-triazol-4-yl)methoxy]benzene-1,2-dicarbonitrile: crystal structure, Hirshfeld surface analysis and energy-minimization calculations - Norzianah Shamsudin,; Tan, Ai Ling; Young, David J.; Jotani, Mukesh M.; Otero-de-la-Roza, Alberto; Tiekink, Edward R. T. * (International Union of Crystallography, 2016)
In the solid state, the title compound, C18H13N5O, adopts a conformation whereby the phenyl ring and methoxy-benzene-1,2-dicarbonitrile residue (r.m.s. deviation of the 12 non-H atoms = 0.041 Å) lie to opposite sides of the central triazolyl ring, forming dihedral angles of 79.30 (13) and 64.59 (10)°, respectively; the dihedral angle between the outer rings is 14.88 (9)°. This conformation is nearly 7 kcal mol-1 higher in energy than the energy-minimized structure which has a syn disposition of the outer rings, enabling intramolecular [pi]-[pi] interactions. In the crystal, methylene-C-H...N(triazolyl) and carbonitrile-N...[pi](benzene) interactions lead to supramolecular chains along the a axis. Supramolecular layers in the ab plane arise as the chains are connected by benzene-C-H...N(carbonitrile) interactions; layers stack with no directional interactions between them. The specified intermolecular contacts along with other, weaker contributions to the supramolecular stabilization are analysed in a Hirshfeld surface analysis.